Relationship between significant coronary artery disease and coronary artery anomalies - NADİR, AYDIN; BİRDANE, ALPARSLAN; Yazici, Huseyin Ugur; AYDAR, YÜKSEL; Nadir, AYDIN; Senol, Utku; Tasal, Abdurrahman; Goktekin, Omer; ATA, NECMİ (My University, 2013)
Aim: In the present study we aimed to investigate the frequency and types of coronary artery anomalies (CAAs) and their correlation with coronary artery disease (CAD).